2013
DOI: 10.1089/vbz.2012.0997
|View full text |Cite
|
Sign up to set email alerts
|

Factors AffectingBrucellaspp. Blood Cultures Positivity in Children

Abstract: Brucella infections have a wide spectrum of symptoms especially in children, making the diagnosis a complicated process. The gold standard for the final diagnosis for brucellosis is to identify the Brucella spp. isolated from blood or bone marrow cultures. The main purpose of this work was to evaluate the factors affecting the isolation of Brucella spp. from blood cultures. In our study, the ratio of fever, presence of hepatomegaly, and splenomegaly were found to be higher in the bacteremic group. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 23 publications
6
22
1
Order By: Relevance
“…Consistent with previous studies, we found that acute brucellosis was usually associated with a high rate of Brucella bacteremia. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we found that acute brucellosis was usually associated with a high rate of Brucella bacteremia. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Anemia, leukopenia, and especially in endemic areas thrombocytopenia can be detected in the complete blood count in patients with brucellosis [19][20][21][22]. Additionally, it has been reported that increased levels of inflammatory markers such as CRP, ESR, and liver enzymes such as AST, ALT, and GTT in biochemical tests can support the diagnosis [23][24][25][26][27]. A study by Bozdemir et al reported that increased NLR values could be used as an indicator of inflammation in childhood brucellosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Brucellemic patients frequently present with higher fever than those with no demonstrable bacteremia (30). However, because brucellae are pathogens with relatively low virulence in humans, the inflammatory response may be attenuated, and the organism may be recovered from paucisymptomatic and even afebrile patients (31).…”
Section: Culture Detection Of Brucellae Blood Culturesmentioning
confidence: 99%